Early Esophageal Cancer Specific Survival Is Unaffected by Anatomical Location of Tumor: A Population-Based Study - Rajan N. Amin; Samip J. Parikh; Venu Gopala Reddy Gangireddy; Praveen Kanneganti; Swathi Talla; Sumanth Daram (Canadian Journal of Gastroenterology and Hepatology)
Background. Approximately one-fifth of all esophageal cancer cases are defined as early esophageal cancer (EEC). Although endoscopic therapy (ET) has been shown to be equally effective as esophagectomy (EST) in patients with EEC, there is little information comparing the survival outcomes of the two therapies based on anatomical location. Methods. A population-based study was conducted and the data was obtained from Surveillance, Epidemiology, and End Results program. Patients with EEC (i.e., stages Tis and T1a) and treated with either ET or EST were analyzed to compare EEC-related survival for three different locations of tumor. Results. The overall EEC-specific 1-year and 5-year mean (±SE) survival rates were 11.66±0.05 and 52.80±0.58 months, respectively. Tumors located in lower third had better 5-year survival compared to those located in middle third (83.50% versus 73.10%, p<0.01). However, when adjusted for age, race, gender, marital status, grade, stage of tumor, histological type, and treatment modality, there was no significant difference. Conclusion. The EEC-specific 1-year or 5-year adjusted survival did not differ by anatomic location of the tumor. Therefore, ET might serve as a minimally invasive yet effective alternative to EST to treat EEC.